VARIATIONist Linguistics meets CONTACT Linguistics - Lenz, Alexandra N.; Maselko, Mateusz (2020)
The current volume is dedicated to the inherently heterogeneous nature of language(s) as seen from the perspective of variationist linguistics and contact linguistics, which became established and internationally recognized sub-disciplines of (socio)linguistics during the latter half of the 20th century. Over the last few years, each paradigm has broadened the spectrum of the topics under investigation considerably, but there has not yet been an extensive and satisfactory exchange between the two scientific fields named. The present volume aims at giving an insight into the complex synergy between occurring linguistic contact constellation, on the one hand, and variation in the parlance, on the other hand.